"Because I could not stop for death": phenomenologizing death anxiety among Filipino Older adults. Issue 12 (1st December 2020) - Laguilles-Villafuerte, Salvacion; de Guzman, Allan B.
ABSTRACT: The fear of death and the dying process may be attributed to cognitive, emotional and behavioral buffers of an individual. Recent studies suggest that age plays an important role in the absence or presence of death anxiety among varied groups. The dynamics of death anxiety is attributed to certain cultural factors such as family ties, traditions and faith. While there had been empirical attempts to examine death anxiety among older adults, little is known about the lived experiences of Filipino older adults. This paper argues that a more contextualized perspective is needed relative to acknowledging, preparing and accepting the inevitability of death in a collectivist society such as the Philippines. Hence, this phenomenological inquiry looked into the death anxiety experiences of a select group of twelve (12) Filipino older adults, aged from 62 to 75 years old. From the vertical and horizontal analyses of the narratives shared during a semi-structured interview, a model called Death Anxiety Refraction model was conceptualized. This model captures three interlocking dimensions (context, emotional and actionality) that describe the nature of death anxiety among older adults. Implications of the emerged model to geriatrics, gerontological psychology and educational gerontology are discussed in this paper.